Cotton leaf curl disease - an emerging threat to cotton production worldwide - Sattar, M Naeem; Kvarnheden, Anders; Saeed, Muhammad; Briddon, Rob W (Journal of general virology, 2013)
Cotton leaf curl disease (CLCuD) is a serious disease of cotton which has characteristic symptoms, the most unusual of which is the formation of leaf-like enations on the undersides of leaves. The disease is caused by whitefly-transmitted geminiviruses (family Geminiviridae, genus Begomovirus) in association with specific, symptom-modulating satellites (betasatellites) and an evolutionarily distinct group of satellite-like molecules known as alphasatellites. CLCuD occurs across Africa as well as in Pakistan and north-western India. Over the past 25 years, Pakistan and India have experienced two epidemics of the disease, the most recent of which involved a virus and satellite that are resistance breaking. Loss of this conventional host-plant resistance, which saved the cotton growers from ruin in the late 1990s, leaves farmers with only relatively poor host plant tolerance to counter the extensive losses the disease causes. There has always been the fear that CLCuD could spread from the relatively limited geographical range it encompasses at present to other cotton-growing areas of the world where, although the disease is not present, the environmental conditions are suitable for its establishment and the whitefly vector occurs. Unfortunately recent events have shown this fear to be well founded, with CLCuD making its first appearance in China. Here, we outline recent advances made in understanding the molecular biology of the components of the disease complex, their interactions with host plants, as well as efforts being made to control CLCuD.